Stressors and Supports: Experiences of Young Black People with Diverse Sexual Identities in the United States - Sandra Lynn Barnes (Religions)
This qualitative study examines common stressors and support mechanisms in the lives of a group of 76 young Black members of the LGBTQIA community ages 18–30 years old based on questions to gauge common conflict or problems in their lives, personal support networks, and experiential reflections. Findings are based on the Structure versus Agency discourse and content analysis. In addition to individual agency, results document experiences navigating structural forces that are often intersectional in nature, the importance of family and friendship networks as a mitigating structural force against stressors, as well as the role of religion and/or spirituality in fostering agency.